2000
DOI: 10.1021/jf990543w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil pH−Sorption Interactions on Imazethapyr Carry-over

Abstract: Soil pH affects imazethapyr sorption-desorption, which in turn can affect persistence and bioavailability. Long-term imazethapyr carry-over has been observed in soil that is below pH 6.5, resulting in significant sugarbeet damage. Imazethapyr concentration decreased rapidly in field soil, regardless of pH. Despite similar amounts of imazethapyr remaining in aged soils at different pH levels, there were differences in bioavailability, which can be explained by sorption-desorption. At low pH more imazethapyr was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 13 publications
2
45
1
12
Order By: Relevance
“…It is known that its adsorption determines how much of the herbicide will be sorbed to the soil matrix and how much is available in the solution. For weak acid herbicides low soil pH provides higher adsorption (Bresnaham et al, 2000;Madani et al 2003;Oliveira et al, 2004), which are less available to plants. The rice soils of Rio Grande do Sul state are predominantly acidic in its natural condition, and approximately 50% of them have pH lower than 5 (Anghinoni et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that its adsorption determines how much of the herbicide will be sorbed to the soil matrix and how much is available in the solution. For weak acid herbicides low soil pH provides higher adsorption (Bresnaham et al, 2000;Madani et al 2003;Oliveira et al, 2004), which are less available to plants. The rice soils of Rio Grande do Sul state are predominantly acidic in its natural condition, and approximately 50% of them have pH lower than 5 (Anghinoni et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Long-term imazethapyr carryover has been observed in soil that is below a pH of 6.5, resulting in significant sugar beet damage. 16) Selectivity in soybeans is attributed to a rapid detoxification via hydroxylation and glycosylation in the course of days [1][2][3][4][5][6]31) and the persistence of the imazethapyr herbicide in the soil is very long in soils with low pH. 30) In another study conducted in soils with a high pH (alkaline, cracking clay, pH 8.6) no residue was found in the top 10 cm of soil; however, 0.6-1.6 ng/g of imazethapyr was reported at 20-40 cm soil depths after four months of imazethapyr application.…”
Section: Terminal Residues Of Imazethapyr In Soilmentioning
confidence: 99%
“…15) Due to leaching and persistence that may damage subsequent rotation crops, some researchers have recommended re-cropping periods of 6-34 months for imazethapyr and have reported that imazethapyr has a rapid initial phase of degradation, followed by a slower second phase leading to long-term persistence, especially in clay soil. 16,17) A half-life of 18-21 day was reported of imazethapyr in silty clay soil. 18) Stable herbicides may be taken up by plants, which results in unwanted terminal residues.…”
Section: Introductionmentioning
confidence: 99%
“…Flucarbazone dissipation rate in soil is fast and the flucarbazone half-life in different soil types has been reported to range from 6 to 110 days (Eliason et al 2004). However, as is the case with other ALS-inhibiting herbicides (Goetz et al 1990;Anderson & Humburg 1987;Anderson & Barrett 1985;Loux & Reese 1992;Walker & Brown 1983), flucarbazone may persist in soil particularly under the following year, it may damage rotational crops as has been reported for various sensitive crops seeded one year after an ALS-herbicide application including canola (Brassica napus L.), flax (Linum usitatissimum L.), lentil (Lens culinaris Medic), oriental mustard (Brassica juncea L.), corn (Zea mays L.), and sugar beet (Beta vulgaris L.) (Bresnahan et al 2000;Moyer et al 1990;Moyer & Esau 1996;Moyer & Hamman 2001).…”
Section: Introductionmentioning
confidence: 99%